PENGARUH DEWAN DIREKSI, DEWAN KOMISARIS, KOMITE AUDIT DAN KEPEMILIKAN INSTITUSIONAL TERHADAP OPINI AUDIT ASUMSI GOING CONCERN - Syarifah Siti Rabiah; Kamaliah -; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The main purpose of this research is examining and knowing the effects of board of directors, board of commissioners, audit committe and institusional ownership to the opinion of audit assumtion of going concern. The population in this study were manufacture firm listing in Indonesia Stock Exchange period 2011-2013, with the population total 136 firms, the sample are taken using purposive sampling method, and there are 31 firm that fullfill the criteria. The data analysis technice which is used in this study is logistic regression. The result of this research show that board of commissioners and audit committe have effect on the opinion of audit assumtion of going concern. Then, board of directors and institusional ownership does not have affect on the opinion of audit assumtion of going concern.Keywords: board of directors, board of commissioners, audit committe, institusional ownership, going concern opinion audit